Talking Stick Learning Model in Fostering EFL Students' Digital Communicative Competence in the 21st Century - bin Tuan Kechik, Tuan Nordin; Nurliah, Nurliah; Limbong, Sunarlia; Sasabone, Luana; Amaliah, Nurul; M, Asia; Asdar, Asdar (CV. Eureka Murakabi Abadi, 2025)
Digital communicative competency has evolved into a must for EFL students in the twenty-first century if they are to connect boldly and appropriately in English via email, video conferences, and messaging apps. This study aims to examine how the Talking Stick learning paradigm affects EFL students' digital communicative competence, or their capacity to communicate confidently, appropriately, and effectively in English across digital platforms. This study used a quantitative research design, using a survey approach. The findings show that all four dimensions had statistically significant improvements, with the highest gain in Confidence in Digital Communication, and displayed a statistically significant increase. Confidence in Digital Communication (M difference = 0.91) had the highest significant mean improvement; closely followed was Clarity in Online Expression (M difference = 0.89). The observed variations were statistically significant since all p-values were less than 0.05. These results suggest that in EFL environments, the Talking Stick model efficiently supports several aspects of digital communication. This study concludes that the Talking Stick learning model effectively enhances EFL students' digital communicative competence, improving key areas such as confidence, clarity, appropriateness, and engagement in online communication.